The Influence of Change and Individual Characteristics on Resistance to Change: A Study among Employees of Pacnet Global (M) - Kavitha, Sariadaran (2009)
The purpose of this study was to investigate employee's reaction towards resistance to change. Another aim was to find out their self efficacy characteristics towards change. The study was conducted in Pacnet Global (M) and questionnaires were sent out to 108 samples and all responses were received. The results of the study were that resistance to change negatively related to Pacnet Global (M) employees as most of them happy with the change. It was discovered that there are some employees plausible resist changing. The principal conclusion was that resistance to change is all depending on a individual perspective and their personal behavior.